Using the shuttlebox experimental design to determine temperature preference for juvenile Westslope Cutthroat Trout (Oncorhynchus clarkii lewisi). Issue 1 (18th April 2018) - Macnaughton, Camille J; Kovachik, Colin; Charles, Colin; Enders, Eva C
Abstract : To determine the temperature preference for juvenile Westslope Cutthroat Trout, we conducted an experiment using an automated shuttlebox design (Loligo® Systems), whereby fish regulated ambient temperature by freely moving between cooling and warming chambers. The duration of the acclimation and experimental periods and effect of photoperiod were also evaluated, guiding future thermal preference experiments. Abstract: Temperature preference for various fishes has often been used as a proxy of optimal temperature for growth and metabolism due to the ease of obtaining preferred temperature zones in laboratory experiments. Several laboratory designs and methods have been proposed to examine preferred temperature zones, however, differences between them (i.e. thermal gradients vs. static temperatures in chambers and duration of acclimation/experimental periods) have led to varying measurements, precluding comparisons between experiments, species and/or life-stages. Juvenile Westslope Cutthroat Trout ( Oncorhynchus clarkii lewisi ), a species listed as threatened in Alberta and of special concern in British Columbia, were tested in an automated shuttlebox experimental design (Loligo® Systems) to determine average and ranges of temperature preference ( T pref ) and occupied temperatures. Previous lab studies suggested that Westslope Cutthroat Trout (WCT) prefer temperatures around 15°C, however, we found that average daytime T pref for lab-reared juvenile WCT was substantially higher at 18.6°C, with occupied temperatures ranging between 11.9°C and 26.0°C throughout the duration of trials. This seems to indicate that despite constant lab-rearing conditions of 12°C, juvenile WCT may tolerate and even prefer warmer water temperatures. The duration of the acclimation period (1h, 12 h and 24 h) did not have an effect on T pref, however, T pref differed significantly for variable trial durations (12 h, 24 h and 36 h). A closer look at thermal trends throughout trials revealed that photoperiod significantly influenced T pref, as nighttime temperature preference reached consistently 26°C. Collectively, these results suggest that shuttlebox experiments on WCT need to take into account the photoperiod, as behaviour may drive T pref more so than the duration of acclimation periods.